(untitled) (GEOmedia, 2014)
The GI-N2K project, coordinated by the Katholieke Universiteit Leuven, which began in October 2013, and formed by an international consortium of 31 partners (25 countries) is funded by the Erasmus Lifelong Learning Programme, aims to reformulate the Body of Knowledge in the field of Geographic Information Science and Technology.